Pengaruh Kepemilikan Asing dan Mekanisme Bonus terhadap Transfer Pricing - Ambarita, Dinar (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study is motivated by the increasing concern over transfer pricing practices, particularly among companies with foreign ownership and incentive-based compensation systems. It aims to examine the effect of Foreign Ownership and Bonus Mechanism on Transfer Pricing in Consumer Non-Cyclicals companies. The research adopts a quantitative approach, utilizing secondary data derived from the financial statements of companies listed on the Indonesia Stock Exchange (IDX). A purposive sampling method was employed to select the sample. The analysis techniques include descriptive statistics, multiple linear regression, panel data regression analysis, model selection using the Random Effect Model, classical assumption testing, and hypothesis testing with the aid of E-Views version 12. The findings reveal that Foreign Ownership and Bonus Mechanism together significantly influence Transfer Pricing. However, when examined individually, only Foreign Ownership shows a significant effect, while the Bonus Mechanism does not. This suggests that foreign-owned firms are more inclined to engage in transfer pricing, likely for tax or regulatory advantages. These findings underscore the importance of implementing stricter oversight and regulations on foreign-owned entities to curb potentially harmful transfer pricing activities.